2014
DOI: 10.1186/1471-2164-15-967
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional responses of PBMC in psychosocially stressed animals indicate an alerting of the immune system in female but not in castrated male pigs

Abstract: BackgroundBrain and immune system are linked in a bi-directional manner. To date, it remained largely unknown why immune components become suppressed, enhanced, or remain unaffected in relation to psychosocial stress. Therefore, we mixed unfamiliar pigs with different levels of aggressiveness. We separated castrated male and female pigs into psychosocially high- and low- stressed animals by skin lesions, plasma cortisol level, and creatine kinase activity obtained from agonistic behaviour associated with regro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
1
3
2
Order By: Relevance
“…Coping style and indirect genetic effects Previous studies have shown that pigs diverging in coping style, that is the way they deal with stress as part of their personality, differ in immune characteristics, including NAb to KLH, and/or modulate the effects of environmental factors on immune responses (Schrama et al, 1997;Bolhuis et al, 2003;Oster et al, 2014;Reimert et al, 2014a). No effects on levels of autoantibodies binding MBP and PC were, however, found in this study.…”
Section: Gender Effectscontrasting
confidence: 72%
“…Coping style and indirect genetic effects Previous studies have shown that pigs diverging in coping style, that is the way they deal with stress as part of their personality, differ in immune characteristics, including NAb to KLH, and/or modulate the effects of environmental factors on immune responses (Schrama et al, 1997;Bolhuis et al, 2003;Oster et al, 2014;Reimert et al, 2014a). No effects on levels of autoantibodies binding MBP and PC were, however, found in this study.…”
Section: Gender Effectscontrasting
confidence: 72%
“…This may be related to the high oxidative metabolism of the LT ( Hocquette et al, 2012b ), which makes it more prone to changes in oxidative status and therefore susceptible to stress. Muscle gene expression in response to stress likely also depends on sex ( Oster et al, 2014 ), the nature and intensity or duration of the stress, and breed, which may explain some differences in the results of our study and a previous study on Angus animals ( Zhao et al, 2012 ). Nevertheless, the regulation of genes involved in carbohydrate, lipid, and protein metabolism is likely to occur in many cases, as observed in this study, as well as in other studies on cattle ( Buckham Sporer et al, 2007 ; Zhao et al, 2012 ) and pigs ( Davoli et al, 2009 ).…”
Section: Discussioncontrasting
confidence: 75%
“…These genes include Heat shock 27kDa protein 1 ( HSPB1 ) (logFC -2.5, FDR 0.005) and Thyroid hormone receptor interactor 11 ( TRIP11 ) (logFC -1.55, FDR 0.01), both of which increase in expression in response to stress as compared to controls. TRIP11 has been previously implicated in the stress response [56], yet its function in the testes is currently unknown. The full table of differential expression results for the male testes in response to stress is available at https://git.io/vDBTw.…”
Section: Resultsmentioning
confidence: 99%